If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -114q = -1176 + -16q Solving -114q = -1176 + -16q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '16q' to each side of the equation. -114q + 16q = -1176 + -16q + 16q Combine like terms: -114q + 16q = -98q -98q = -1176 + -16q + 16q Combine like terms: -16q + 16q = 0 -98q = -1176 + 0 -98q = -1176 Divide each side by '-98'. q = 12 Simplifying q = 12
| A=18W-W^2 | | ix-3x=0 | | 2(x-4)=3x-9-x | | y-2=4/5(x-3) | | (2x-1)(5x-5)= | | 4r-4=(r-4)(r-4) | | 0.6x-1.9y+3.2=0 | | 160=3x+y | | -9y+19=4y-7 | | 1-4.9x^2=0 | | (w-4)/4w=1/5 | | 12y-7+1+4y= | | ix=3x | | 7-2y=10-6y+4y | | x(x-3)=16/3 | | -3(5u-2)+5u=4(u+4) | | 3(4y)=24 | | 6(x-3)=9x-24 | | 2(6d+3)=18-48+9d | | X+(x-5)=20 | | 10.2u+0.5=2.5u-0.3(u-7) | | 2x^2+12x+19=x^2+8x+16 | | X^2+10+25=245-2x | | 4x+20=2x+34 | | 2x^3+3x^2+5x+2=0 | | -22=5(u-2)-8u | | F(x)=log(x-4)-3 | | 3x+1x+24=28x | | 10x-(12x+8)=12 | | (x-1)*(x-1)*(x+4)=0 | | 21x^2=-17x+8 | | H=4+63t-63t^2 |